Aggressive recurrences determine oncologic outcomes after resection of liver metastases from primary right colon cancer: Results of a case-control study. Issue 4 (April 2021) - Zimmitti, Giuseppe; Panettieri, Elena; Ardito, Francesco; Mele, Caterina; Maria, Vellone; Rosso, Edoardo; Nuzzo, Gennaro; Giuliante, Felice
Abstract: Background: Despite recent studies suggest that, among patients operated on for colorectal liver metastases (CLM), the primary tumor location may impact on postoperative survivals, results are still contrasting. Objective: evaluating survivals (overall (OS) and (DFS)) following liver resection of CLM from Right colon Cancer (RcC-CLM) versus Left colon Cancer (LcC-CLM), among patients undergoing preoperative chemotherapy (pCHT), identifying survival predictors, and investigating impact of recurrent disease pattern and management on survival. Methods: Among 727 patients operated for CLM(1989–2016), after excluding patients with primary transverse colon/rectum tumor and patients not receving pCHT, 297 patients were identified. Among them, 81 with RcC-CLM were matched 1:1 with LcC-CLM, according to CLM number and diameter, disease-free interval between primary tumor and CLM diagnosis, primary tumor N-status, and the presence of extrahepatic disease. Results: Overall, 66.7% of patients had multiple CLM, 21% had CLM>5 cm, 82.7% had DFI<12 months, 67.9% had N+ primary tumor, and 11.1% had extrahepatic disease at time of hepatectomy. RcC-CLM patients were similar to LcC-CLM in terms of demographic, clinical, perioperative, and pathologic characteristics. Patients operated for RcC-CLM, compared to LcC-CLM, had significantly shorter 5y-DFS(18% versus 39%) and 5y-OS(38% vs 65%). At multivariate analysis, being operated for RcC-CLM, compared to LcC-CLM, was the strongest predictor of recurrence (Hazard Ratio:2.265, p < .001) and death (HR:2.234, p = .001). Among 107 patients experiencing recurrent disease, curative recurrence resection was associated with higher 5y-OS(64% vs 17%; p < .001). However, recurrence resection was less frequently feasible among RcC-CLM(26%) patients, compared to LcC-CLM(44%, p = .05). Conclusions: resection of RcC-CLM, compared to LcC-CLM, is associated with worse survivals, probably related to a different pattern of recurrence precluding recurrence resection among RcC-CLM patients.